Motives for moral behavior among Malay Muslim students secondary school - Yasin, Maizura; Abdullah, Nur Surayyah Madhubala; Roslan, Samsilah; Abdul Wahat, Nor Wahiza (Universitas Islam Negeri Syarif Hidayatullah, 2018)
This paper provides an overview of the motives underpinning Malay Muslim secondary school students’ moral behavior in Malaysia in their daily life. The paper is based on a qualitative case study employing purposive sampling into the motives behind Malay Muslim students’ moral behavior. The study of eight Form Four Malay Muslim students in a school in Malaysia identified six themes associated with the motives for moral behavior. The findings illustrate that Malay Muslim students have different motives for their moral behavior and that these are linked to moral reasoning. It offers an insight into what motivates Malay Muslim students who are in a family structure where religion is a strong influence of their moral behavior. It illustrates how family background, religious values and personal experiences shape the reasons for behaving morally. A key implication of the findings for Moral Education is in educating students to behave morally, teachers in particular Moral Education teachers should consider that the motivation for the action may differ based on certain aspects of the student's background that influence their beliefs about what is right and good. Teachers should also identify the prevailing motives and their influences on students’ moral behavior by facilitating reflection on their behavior and the choice the right motives in morality.